An electrochemical approach to evaluating surface coatings - Demiroren, Hulya; Buytoz, Soner (Inderscience Enterprises Ltd, 2021)
In order to understand the influence of metal carbides and niobium carbides on electrochemical behaviour of Fe-based composite powder and FeNb powder coatings were added. Above mentioned composite layer was prepared on a medium carbon steel surface by using GTAW coating technique. The morphology of the coatings' surface was analysed by optical microscope, scanning electron microscope (SEM) equipped with an energy-dispersive spectroscopy (EDS) and X-ray diffractometer (XRD). Then the samples were exposed to seawater. Electrochemical impedance spectroscopy (EIS) method with triple electrode system was used in order to obtain Bode and Nyquist diagrams. Ag/AgCl electrode is used as reference electrode, and platin plate is counter electode in this system. As a result, adding NbC has harmful effect on the electrochemical behaviour of FeCrC coating powder.
Keywords: Fe-based composite; Cr7C3 carbide; NbC carbide; EIS; Nyquist plot